Productionof catalytic and non-catalytic gases from pyrolysis of municipal solid waste (MSW) - Tursunov, Obid
Municipal Solid Waste (MSW) is primarily waste produced by the household, but also includes some commercial and industrial waste that is similar in nature to household waste and has been deposited in municipal landfill site, causing multitude of harmful impacts to the environment and to human beings. Currently, recycling of MSW is an essential issue in many developed and developing countries like in Malaysia as well. One of the effective techniques for MSW recycling is pyrolysis. Pyrolysis is the degradation of macromolecular materials with heat in the absence of oxygen. It has both applied and analytical aspects. The development of advanced fast pyrolysis process for gas production has gained much attention in the last decade, because they offer a convenient way to convert low value MSW residues into gas yield and value-added products. In this study, pyrolysis process has been used for municipal solid waste recycling into renewable kind of energy. Pyrolysis offer more scope for recovering products from waste than incineration. When MSW is burnt in a modern incinerator the only practical product is energy, whereas the gases, oils and solid char from pyrolysis can be used as a fuel but also purified and used as a feedstock for petro-chemicals and other applications. In addition, catalyst in pyrolysis has been playing significant role to increase product yields. However, a few literatures were found on catalyst in pyrolysis process. This study focused on gas production from pyrolysis process of municipal solid waste by using three types of catalysts (zeolite, raw dolomite and calcined dolomite). Thus, this study focused on gases (HC, CO and CO2) analysis from pyrolysis of municipal solid waste (MSW) with catalysts zeolite, four types of calcined (700oC/4h, 800oC/5h, 900oC/4h and 950oC/3h) and raw dolomite as catalyst, and also non catalytic pyrolysis of MSW. Calcined dolomite 950oC/3h and 800oC/5h were selected as suitable catalyst among others for CO and CO2 production. Research project has been investigated in a “catatest” downstream fixed – bed reactor over the temperature range between of 30 – 750oC. Gas production from pyrolysis of MSW varied in the range of 35 – 57 mol%. The results indicated the presence of calcined dolomite influenced significantly the product yields and gas composition in pyrolysis process, and revealed essential catalytic performance on increasing gas yield and decreasing oil yield and char yield comparing to zeolite and non – catalytic pyrolysis process. A higher temperature of 550 – 750oC resulted in a higher conversion of MSW into gas production with a greatly increasing of CO and slight increasing of CO2 contents.